2019
DOI: 10.1111/bjet.12780
|View full text |Cite
|
Sign up to set email alerts
|

Educational technology research trends in Turkey from a critical perspective: An analysis of postgraduate theses

Abstract: The aim of this study is to explore the research trends in the context of postgraduate programmes in the field of Educational Technology (ET) in Turkey between 1996 and 2016, and to uncover the possible factors that influence these trends from the perspective of ET faculty members. This study was informed by critical theory and employed the critical inquiry method. In the first phase, content analysis technique was used in order to explore trends in research methods and topics in theses completed in ET postgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…For instance, just like today, there were concerns about the role of the educator and the fear educators had of being replaced by educational technology (Elly 1992;Spencer 1999) and questions about how people learn with educational technology (Hranstinski & Keller 2007); and the effectiveness of educational technology (Delgado et al 2015;Morrison et al 2010;Spencer 1999). Moreover, there was an extensive focus on media and delivery methods (Clark 1983;Kozma 1991), from which the influence and dominance of the positivist paradigm emerged (Kara Aydemir, & Can 2019;Hew et al 2007;Hranstinski & Keller 2007;Reeves & Oh 2017), replacing and neglecting critical theoretical perspectives (Reeves & Oh 2017) and more importantly, the human learners. Besides, while it is argued that "there has been a shift from often unquestioning advocacy of particular technologies to a more critical, theoretical understanding" (Weller 2020), others have argued that computer-based and online technologies and their integration into education created great enthusiasm, that the theoretical underpinning of educational technology was largely ignored (Albirini 2007; Alper & Gulbahar 2009; Issroff & Scanlon 2002;Oliver 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, just like today, there were concerns about the role of the educator and the fear educators had of being replaced by educational technology (Elly 1992;Spencer 1999) and questions about how people learn with educational technology (Hranstinski & Keller 2007); and the effectiveness of educational technology (Delgado et al 2015;Morrison et al 2010;Spencer 1999). Moreover, there was an extensive focus on media and delivery methods (Clark 1983;Kozma 1991), from which the influence and dominance of the positivist paradigm emerged (Kara Aydemir, & Can 2019;Hew et al 2007;Hranstinski & Keller 2007;Reeves & Oh 2017), replacing and neglecting critical theoretical perspectives (Reeves & Oh 2017) and more importantly, the human learners. Besides, while it is argued that "there has been a shift from often unquestioning advocacy of particular technologies to a more critical, theoretical understanding" (Weller 2020), others have argued that computer-based and online technologies and their integration into education created great enthusiasm, that the theoretical underpinning of educational technology was largely ignored (Albirini 2007; Alper & Gulbahar 2009; Issroff & Scanlon 2002;Oliver 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Introduction: Tendency research conducted in a field of science is important in terms of shedding light on how a field has been transforming from past to present, especially in social fields. From defining to recognizing a new field such as Instructional Technology (Gagne, 1986;Reiser, 2001), from technologies that direct researchers to current theories (Ross, Morrison, & Lowther, 2010), and factors affecting these trends (Kara Aydemir & Can, 2019) will guide all readers, especially researchers. Such studies also contribute to the development of a current research agenda.…”
Section: Systematic Analysis Of International Computer and Instructionalmentioning
confidence: 99%
“…Eğilim çalışmaları Öğretim Teknolojileri gibi gelişen teknolojilerden de etkilenen bir alan için de ayrıca önem taşımaktadır. Bu kapsamda eğilim çalışmaları Öğretim Teknolojileri alanının tanımlanmasından tanınmasına (Gagne, 1986;Reiser, 2001), araştırmalara yön veren teknolojilerden güncel kuramlara (Ross, Morrison, & Lowther, 2010) ve bu eğilimleri etkileyen faktörlere (Kara Aydemir & Can, 2019) kadar birçok husus başta araştırmacılar olmak üzere tüm okuyucu kitlesine yol gösterici olmaktadır (Cohen, Manion, & Morrison, 2007). Bu tür çalışmalar aynı zamanda araştırmacıların güncel bir araştırma gündemi oluşturmasına da katkı sağlarlar.…”
Section: Introductionunclassified
“…Chen, X. et al demonstrated the developments in the field of educational technology based on a bibliometric analysis of the British Journal of Educational Technology and highlighted the hot spots of educational technology research such as blended learning, online social communities, and mobile-assisted language learning [19]. Kara Aydemir et al explored the trend of educational technology research in Turkey and also analyzed the influencing factors of the trend based on ET teachers' perspectives and showed that the influencing factors include the social impact of the research, individual interests and skills, disciplinary and departmental cultures, and feasibility considerations [20].…”
Section: Introductionmentioning
confidence: 99%